Dimerization of NF-KB2 with RelA(p65) regulates DNA binding, transcriptional activation, and inhibition by an I kappa B-alpha (MAD-3). - Duckett, C S (1993)
Inducible expression of human immunodeficiency virus (HIV) is regulated by a cellular transcription factor, nuclear factor kappa B (NF-kappa B). NF-kappa B is composed of distinct subunits; five independent genes, NFKB1(p105), NFKB2(p100), RelA(p65), c-rel and relB, that encode related proteins that bind to kappa B DNA elements have been isolated. We have previously found that NFKB2(p49/p52) acts in concert with RelA(p65) to stimulate the HIV enhancer in Jurkat T-leukemia cells. Here we examine the biochemical basis for the transcriptional regulation of HIV by NFKB2. Using Scatchard analysis, we have determined the dissociation constants of homodimeric p49 and heterodimeric p49/p65 for binding to the HIV kappa B site. p49 has a approximately 18-fold-lower affinity for the HIV kappa B site (KD = 69.1 pM) than does the approximately 50-kDa protein NFKB1(p50) derived from p105 (KD = 3.9 pM). In contrast, the affinity of heterodimeric NFKB2(p49)/RelA(p65) for this site is approximately 6-fold higher (KD = 11.8 pM) than that of p49 alone. Consistent with these findings, in vitro transcription was stimulated 18-fold by the addition of preformed, heterodimeric NFKB2(p49)/RelA(p65) protein. Transcriptional activation of the HIV enhancer was also subject to regulation by recently cloned I kappa B-alpha(MAD-3). Recombinant I kappa B-alpha(MAD-3) inhibited the DNA binding activity of p65, p49/p65, and p50/p65 but stimulated the binding of NFKB2(p49) or NFKB1(p50). Functional activation of an HIV reporter plasmid by p49/p65 in transiently transfected Jurkat T-leukemia cells was also inhibited by coexpression of MAD-3. These data suggest that binding of the NFKB2 subunit to the HIV enhancer is facilitated by RelA(p65) and that this NFKB2(p49)/p65 heterodimeric complex mediates transcriptional activation which is subject to regulation by MAD-3.